1993
DOI: 10.1016/s0022-5347(17)36031-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Proliferating Cell Nuclear Antigen (Pcna)/Cyclin in Human Prostate Adenocarcinoma

Abstract: Tissue specimens from 12 patients with adenocarcinoma of the prostate and 7 patients with benign prostate hypertrophy were stained by an indirect immunoperoxidase method using antiproliferating cell nuclear antigen (PCNA) monoclonal antibody. The PCNA labeling index was determined by counting the number of PCNA-labeled cells in the tissue sections. Average PCNA labeling index of the benign prostate hypertrophy was 1.2 +/- 0.5%. Poorly differentiated tumors averaged 7.6 +/- 3.9% labeling versus 4.6 +/- 1.3% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…Because many prostatic tumors have an increased rate of proliferation relative to surrounding tissue [22,23], the incorporation of [ 3 H]thymidine and constitutive levels of the proliferation marker ODC were compared in the control and the NbE-neu-T clones. All four clones demonstrated an increase in [ 3 H]thymidine incorporation between days 1 and 7 of the study (P ≤ 0.001; Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many prostatic tumors have an increased rate of proliferation relative to surrounding tissue [22,23], the incorporation of [ 3 H]thymidine and constitutive levels of the proliferation marker ODC were compared in the control and the NbE-neu-T clones. All four clones demonstrated an increase in [ 3 H]thymidine incorporation between days 1 and 7 of the study (P ≤ 0.001; Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation of prostatic carcinoma increases during disease progression [22,23], and initially, this proliferation is dependent on the presence of androgens. However, during the hormone-insensitive phase of the disease, proliferation must be regulated or stimulated by other as-yet-unidentified pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Visakorpi [17] mentioned that there was no close correlation between the PCNA index and glandular differentiation, whereas Nemoto et al [18] reported a good correlation between them. Harper et al [16] also reported that the PCNA index was associated with the Gleason grade.…”
Section: Discussionmentioning
confidence: 99%
“…A number of malignant tumors have been studied with the PCNA antibody [9][10][11][16][17][18], and it has been dem onstrated that in some malignant tumors the PCNA index is closely correlated with prognosis [9,10,16]. In this study, we also compared the PCNA index of prostatic car cinomas with both the clinicopathological characteristics and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many prognostic markers have been evaluated [6][7][8]. Two, p53 and Ki-67, have recently received increased attention and are the focus of this report.…”
Section: Discussionmentioning
confidence: 99%